(untitled) (Medical Forum Monthly, 2020)
Objective: To evaluate and compare the levels of serum glutamyl transferase, HbA1C, fasting blood glucose and postprandial blood glucose in diabetics with and without peripheral neuropathy. Study Design: Cross sectional comparative study. Place and Duration of Study: This study was conducted at the Department of Medicine, Niazi Medical & Dental College Sargodha from March 2020 to May 2020. Materials and Methods: This was an exploratory study comprised of 80 type-2 diabetic patients and they were divided into two groups. Group A contained 40 patients with no peripheral neuropathy while Group-B consisted of 40 peripheral neuropathic patients. Results: In Group-A, 35 (87.5%) had serum GGT up to 55 U/L while 5 (12.5%) patients had > 55 U/L and in Group-B, 9 (22.5%) had serum GGT up to 55 U/L while 31 (77.5%) patients had > 55U/L (p=0.001). The mean serum gamma glutamyl transferase of peripheral neuropathy diabetics was 30.97±7.93 U/L and 75.25±12.63 U/L in peripheral neuropathy diabetics (p=0.001). Conclusion: Majority patients with PN had raised serum gamma glutamyl transferase while normal gamma glutamyl transferase levels were observed among most of the patients without peripheral neuropathy.